Fossil musculature of the most primitive jawed vertebrates - Trinajstic, Kate; Sanchez, S.; Dupret, V.; Tafforeau, P.; Long, J.; Young, G.; Senden, T.; Boisvert, C.; Power, N.; Ahlberg, P.E. (The American Association for the Advancement of Science, 2013)
The transition from jawless to jawed vertebrates (gnathostomes) resulted in the reconfiguration of the muscles and skeleton of the head, including the creation of a separate shoulder girdle with distinct neck muscles. We describe here the only known examples of preserved musculature from placoderms (extinct armored fishes), the phylogenetically most basal jawed vertebrates. Placoderms possess a regionalized muscular anatomy that differs radically from the musculature of extant sharks, which is often viewed as primitive for gnathostomes. The placoderm data suggest that neck musculature evolved together with a dermal joint between skull and shoulder girdle, not as part of a broadly flexible neck as in sharks, and that transverse abdominal muscles are an innovation of gnathostomes rather than of tetrapods.